Recording Social Prestige. Local Authorities and Political use of the Internet and Cell Phone in the Community of Yanque (Caylloma, Arequipa) - Sánchez, Mario (2019)
This paper analyzes the role played by the Internet and the cell phone (new ICT) in the registration of social prestige made by local authorities in rituals and festivities of the community of Yanque in the Colca Valley (province of Caylloma, department of Arequipa). The Internet and the cell phone, far from disintegrating the stratified society and the traditional local culture of Yanque, reaffirm and reinforce its validity, because those who use the new ICT to achieve or maintain their social prestige are only those who have accumulated different forms of power (money, lands, objects and religious knowledge, educational titles), accentuating the social differences existing in the village. Nine months of fieldwork were carried out between July 2014 and February 2017.